PKM. PENINGKATAN KEMAMPUAN MENULIS ARTIKEL ILMIAH SAINS MELALUI KEGIATAN PENGABDIAN MASYARAKAT PADA GURU SD NEGERI APUAN BANGLI - I Made Subrata; I Made Darmada; Gusti Ayu Made Puspawati (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Scientific work is a published written report that discloses the results of research or studies carried out by a person or team by fulfilling scientific principles and ethics adhered to by the scientific community. Scientific publications are currently experiencing very significant changes, from where the initial format of using print media has changed to electronic media. The purpose of this community service is to improve the ability of teachers to write scientific articles in the field of science at SD Negeri Apuang Bangli. There are 3 main activities in this service, namely the first meeting for training in writing scientific articles by providing examples and critical review of how to write scientific articles. The second activity is by giving assignments to make the core points of writing scientific scientific articles, and the third activity is carrying out mentoring to provide scientific scientific article consultations that are made according to the intended journal template. Based on the evaluation of the implementation of community service activities and the results of the normalized gain test it appears that there has been an increase in the ability to write science scientific articles for elementary school teachers through this community service activity of 0.75 (high category). The conclusion from this community service activity is that there has been an increase in the ability to write scientific scientific articles for teachers of SD Negeri Apuan Bangli.